2014
DOI: 10.1002/micr.22228
|View full text |Cite
|
Sign up to set email alerts
|

Combined composite osteofasciocutaneous fibular free flap and radial head arthroplasty for reconstruction of the elbow joint

Abstract: Reconstruction of the radial head can be complicated in cases of wide resection, particularly in those cases including the proximal radial shaft. In such cases, radial head replacement may not be possible because of lack of adequate bone stock. Here, we report the use of a radial head prosthesis incorporated with a vascularized fibula for immediate anatomic restoration of the forearm and elbow. We present a case of a pathologic fracture non-union in the proximal radius in a 57-year-old female with a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Fibular flaps are a common vascularized flap that includes both bone and subcutaneous tissue pedicles [ 7 ]. Many of the papers produced have demonstrated the graft being used to bridge the bone in the distal radial, proximal ulnar, and humeral reconstruction, but few have been used to restore joint function [ 5 ]. Scaglioni et al demonstrated the use of vascularized bone grafts in 5 patients with restoration of elbow function: most of the injuries involved the distal humerus or proximal ulna [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibular flaps are a common vascularized flap that includes both bone and subcutaneous tissue pedicles [ 7 ]. Many of the papers produced have demonstrated the graft being used to bridge the bone in the distal radial, proximal ulnar, and humeral reconstruction, but few have been used to restore joint function [ 5 ]. Scaglioni et al demonstrated the use of vascularized bone grafts in 5 patients with restoration of elbow function: most of the injuries involved the distal humerus or proximal ulna [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…ORIF has a limited role in radial head fractures where the fracture cannot be appropriately reduced, the articular congruity cannot be restored, or the elbow does not have adequate motion and stability [ 10 ]. One study demonstrated the fibular free flap and radial head arthroplasty in a patient with nonunion after pathologic fracture [ 5 ]. On one-year follow-up, the patient had active mobility of the elbow joint [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mandible), upper extremity (i.e. humerus, radius, and ulna), lower extremity (i.e. femur, tibia, and calcaneus), and trunk reconstruction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in microsurgery mean that free fibular osteocutaneous flaps are now a useful material for use in forearm reconstruction after injury and malignant tumor resection. [1][2][3][4][5][6][7] However, these materials confer several disadvantages, including a high risk of partial necrosis due to unstable blood supply from the perforators to the skin and the fact that only a limited amount of skin can be harvested. In addition, in free fibular osteocutaneous flaps, the fibula, skin, and vascular pedicle are tightly bound together by the posterior intermuscular septum and the perforating branches that pass through, leading to the disadvantage of a low degree of freedom when setting these structures in place.…”
mentioning
confidence: 99%